CHARACTERIZATION AND STATIC MODELING RESERVOIR A154 AND A155 IN NATA FIELD KUTAI BASIN, EAST KALIMANTAN - Wahyu Dwi Priyantono, Fm
To increase gas production in the Shallow Zone Nata, one way to do this is to perform a characterization of the reservoir, then integrated in a three dimensional modeling, which has never been done before. This study will study the characterization of reservoir sandstones A154 and A155, in Nata Field, which includes the study of facies sedimentation, stratigraphy sikuen, as well as patterns of distribution of rock properties of reservoir sandstones A154 and A155. The results of this study indicate that the reservoir sandstones A154 which has a distributary channel deposition environments, as the delta system, with the remaining reserves of 22:04 Bcf. While the A155 reservoir sandstones deposited in fluvial channel environment, as the delta system, with the remaining reserves of 9.24 Bcf. With the calculation of remaining reserves the reservoir development can be done by drilling wells to the northeast of NATA Field.